Peranan Pendekatan Kualitatif dalam Pemahaman Psikologis: Sebuah Telaah Meta Analisis - Ade Iva Murty (Fakultas Psikologi Universitas Pancasila, 2016)
Qualitative approach in psychology, substantially cannot be detached from the development of social and psychological theory. The paper tries to reposition the role of qualitative methodology in psychology. First, qualitative methodology in psychology remains complementary with quantitative. Especially for the reason that qualitative method ramifications, in intersubjectivity, plays a role for the understandings of psychological phenomena. Second, as the quantitative methods emphazises more on objective measures of research constructs, qualitative methods give ways for exploring and deepening many constructs which for long has been considered uneasy to be studied. Third, qualitative data are innovative and creative, in terms of technological development. Emergent qualitative method enables the possibility of comprehensive understandings of individuals, consciousness, and behavior.